Evaluation of Leachate Recirculation Effect on the Acceleration of Waste Mineralization Process by Using a Coupled Numerical Model - Hailong Liu; Zhen Huyan; Chunyi Cui; Xiang Luo; Xingyao Jiang (Advances in Civil Engineering)
Accelerating the waste mineralization is of great significance to control the settlement of transportation facilities nearby landfills. Mineralized waste can also be used as road construction materials to recycle waste resources and reduce the construction cost of transportation facilities. A biochem-hydro-mechanical-solute migration-coupled model for describing complex interactions in landfills with high kitchen waste content has been developed. The proposed model can consider large leachate production and landfill gas entrapment due to the fast degradation of kitchen waste. The quantitative effects of three leachate recirculation conditions are investigated in this article via a typical landfill cell. According to the simulation results, introducing methanogen into landfills with leachate recirculation can relieve acidification caused by fast hydrolysis of kitchen waste and speed up the mineralization process of landfills with high kitchen waste content significantly. Furthermore, landfill gas generation potential loss and fast degradation compression should be considered in the implementation of leachate recirculation in landfills with high kitchen waste content, which helps to maintain the operation of transportation facilities nearby landfills and improve the economic and environmental benefits of leachate treatment.